Momentum Distribution Functions in a One-Dimensional Extended Periodic Anderson Model - I. Hagymási; J. Sólyom; Ö. Legeza (Advances in Condensed Matter Physics)
We study the momentum distribution of the electrons in an extended periodic Anderson model, where the interaction, Ucf, between itinerant and localized electrons is taken into account. In the symmetric half-filled model, due to the increase of the interorbital interaction, the f electrons become more and more delocalized, while the itinerancy of conduction electrons decreases. Above a certain value of Ucf the f electrons become again localized together with the conduction electrons. In the less than half-filled case, we observe that Ucf causes strong correlations between the f electrons in the mixed valence regime.